Analysis and Exploration of Mobile Microlearning for Vocational High School Students - Wigati, Wigati; Iriani, Tuti; Khaerudin, Khaerudin (Journal of Science and Education (JSE), 2024)
This study aims to analyse the learning needs of Vocational High School students in improving their competence towards software engineering. Therefore, this research was conducted on second grade students of vocational school in Bekasi. Qualitative research method was used to identify students' needs in software engineering learning process. Data collection was conducted by literature review, observation, and in-depth interviews. This research was conducted in collaboration with 28 students who have participated in creative product and entrepreneurship learning and three teachers. The results of this study indicate that students need teaching materials that are concise, interesting and easy to understand. Mobile microlearning is an alternative teaching material needed by students to understand the material of creative products and entrepreneurship in the competence of software engineering expertise. In addition, the use of mobile microlearning teaching materials can be developed with collaborative assignments for students. Thus, this research has implications for student learning innovation in vocational school. Given that the goal of vocational education leads to graduates who are ready to work and entrepreneurship, teaching materials developed based on collaboration can train students to adapt to the work environment and develop themselves independently